Analysis of the social sciences in Latin America: An introduction - Mejía Navarrete, Julio (2020)
The study examines the development of the contemporary social sciences in Latin America and underlines its originality in the creation of theoretical proposals, specially of the power coloniality. It explains the social sciences crisis in the 1980s and the appearance of the new cognitive debate. A process that envelops the revision and criticism of the basic foundations that gave rise to the knowledge since the fifteenth century, and which signifies the advent of another discourse beyond the limits of modernity.